The Reality of AI Usage in English Learning Among English-Major Students at Phu Yen University - Quỳnh, Phạm Như (Electronic Journal of Business and Management, 2025)
This study adopted a quantitative approach to examine the use of Artificial Intelligence (AI) in English language learning among 100 students from the Foreign Languages Department at Phu Yen University. Specifically, it assessed the extent of AI usage, its purposes, advantages, and associated challenges. The findings revealed that all participants (100%) have integrated AI into their learning process, utilizing it for writing enhancement, listening practice, translation, grammar correction, and vocabulary acquisition. Notably, 51.3% of students reported increased confidence and motivation when incorporating AI into their studies. However, the study also identified significant challenges, such as high costs and difficulties in navigating AI tools. These results not only align with previous research but also provide deeper insights into how students at local universities engage with AI technology. The study’s findings offer valuable implications for educators, enabling them to refine teaching methodologies, develop effective learning support tools, and enhance educational quality in an era of rapid technological advancement.